أصول المسائل الفقهية عند الشافعية: دراسة تطبيقية على أصل "النوم ناقض للوضوء" نموذجًا: Foundations of Jurisprudential Issues in the Shafi‘i School: A Case Study on Sleep as a Nullifier of Ablution - Imam Riadi (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
This study explores the concept of “Foundations of Jurisprudential Issues” (Uṣūl al-Masāʾil al-Fiqhiyyah) within the Shāfiʿī school, examining its meaning, usage, and practical application through the principle: "Sleep invalidates ablution (wuḍūʾ) except for one sitting firmly". The research problem lies in the ambiguity of this concept and the lack of independent analytical studies, despite its frequent use in Shāfiʿī legal literature. The precise meaning of the term and the methodological approach of the scholars in dealing with it -through derivation (takhrīj) and branching (tafrīʿ)- have not been clearly defined.The study adopts a descriptive, analytical, and comparative methodology, by examining the writings of Shāfiʿī jurists and uṣūl scholars, analyzing their use of the term, and applying it to a specific jurisprudential principle to identify the relied-upon narrations and trace their juristic implications. The main objectives are to define and clarify the concept of Uṣūl al-Masāʾil al-Fiqhiyyah, and to explain the Shāfiʿī methodology in establishing and applying such foundational principles in jurisprudential reasoning. The research concludes that the Foundations of Jurisprudential Issues refer to the authoritative views of Imām al-Shāfiʿī upon which his followers built subsequent rulings. Recognizing these foundations helps in understanding the structure of the madhhab and the criteria of preference within it. The study also finds that the principle "Sleep invalidates ablution except for one sitting firmly" is based on the new (jadīd) opinion of Imām al-Shāfiʿī and has become a firmly established foundation upon which numerous juristic branches are built.